CREBB repression of protein synthesis in mushroom body gates long-term memory formation in Drosophila. - Lin, H.W.; Chen, C.C.; Jhang, R.Y.; Chen, L.; de Belle, J.S.; Tully, T.; Chiang, A.S. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Learned experiences are not necessarily consolidated into long-term memory (LTM) unless they are periodic and meaningful. LTM depends on de novo protein synthesis mediated by cyclic AMP response element-binding protein (CREB) activity. In Drosophila, two creb genes (crebA, crebB) and multiple CREB isoforms have reported influences on aversive olfactory LTM in response to multiple cycles of spaced conditioning. How CREB isoforms regulate LTM effector genes in various neural elements of the memory circuit is unclear, especially in the mushroom body (MB), a prominent associative center in the fly brain that has been shown to participate in LTM formation. Here, we report that i) spaced training induces crebB expression in MB ?-lobe neurons and ii) elevating specific CREBB isoform levels in the early ?/? subpopulation of MB neurons enhances LTM formation. By contrast, learning from weak training iii) induces 5-HT1A serotonin receptor synthesis, iv) activates 5-HT1A in early ?/? neurons, and v) inhibits LTM formation. vi) LTM is enhanced when this inhibitory effect is relieved by down-regulating 5-HT1A or overexpressing CREBB. Our findings show that spaced training-induced CREBB antagonizes learning-induced 5-HT1A in early ?/? MB neurons to modulate LTM consolidation.